Isotopic evidence for enhanced fossil fuel sources of aerosol ammonium in the urban atmosphere. (July 2018) - Pan, Yuepeng; Tian, Shili; Liu, Dongwei; Fang, Yunting; Zhu, Xiaying; Gao, Meng; Gao, Jian; Michalski, Greg; Wang, Yuesi
Abstract: The sources of aerosol ammonium (NH4 + ) are of interest because of the potential of NH4 + to impact the Earth's radiative balance, as well as human health and biological diversity. Isotopic source apportionment of aerosol NH4 + is challenging in the urban atmosphere, which has excess ammonia (NH3 ) and where nitrogen isotopic fractionation commonly occurs. Based on year-round isotopic measurements in urban Beijing, we show the source dependence of the isotopic abundance of aerosol NH4 +, with isotopically light (−33.8‰) and heavy (0 to +12.0‰) NH4 + associated with strong northerly winds and sustained southerly winds, respectively. On an annual basis, 37–52% of the initial NH3 concentrations in urban Beijing arises from fossil fuel emissions, which are episodically enhanced by air mass stagnation preceding the passage of cold fronts. These results provide strong evidence for the contribution of non-agricultural sources to NH3 in urban regions and suggest that priority should be given to controlling these emissions for haze regulation. This study presents a carefully executed application of existing stable nitrogen isotope measurement and mass-balance techniques to a very important problem: understanding source contributions to atmospheric NH3 in Beijing. This question is crucial to informing environmental policy on reducing particulate matter concentrations, which are some of the highest in the world. However, the isotopic source attribution results presented here still involve a number of uncertain assumptions and they are limited by the incomplete set of chemical and isotopic measurements of gas NH3 and aerosol NH4 + . Further field work and lab experiments are required to adequately characterize endmember isotopic signatures and the subsequent isotopic fractionation process under different air pollution and meteorological conditions. Graphical abstract: Image 1 Highlights: Debate remains over whether agricultural emissions dominate NH3 in urban atmosphere. δ 15 N indicated important contribution of fossil fuel emission to urban aerosol NH4 + . Reducing NH3 emission cobenefits mitigation of haze pollution and nitrogen deposition. Abstract : Fossil fuel emissions dominate source of urban aerosol NH4 + –An isotopic perspective.